O curr??culo da rede estadual paulista de ensino para a disciplina de hist??ria: an??lise, compreens??o e cr??tica dos professores - Souza, ??merson Francisco de (2016)
The state government of S??o Paulo, through the State Secretary of Education, presented and implemented, in 2008, a new curriculum proposal for all schools in the state public school system. In 2010, this curriculum proposal became the official curriculum. This research object of study is the proposed curriculum for the subject of history. Our main concern is to try to understand how history teachers that work in state schools understand, analyze and incorporate the official curriculum objectives, and procedures, and educational concepts, and guidelines into their routine and school practice. Research sources are constituted of official documents that support the proposal such as the base document, the teacher's notebook and student's notebook, the regulatory framework produced by SEE-SP and a set of four interviews with history teachers. Interviews approach teachers??? educational background, their understanding of the curriculum debate, their analysis of the implementation process and how the proposals present in the curriculum have been incorporated in their daily work at school. In this process, the text initially presents different curriculum theories that inform the current debate to show the approximations and distances with the official curriculum. Following, it presents the official curriculum, its foundations, guidelines and structural axes. At the end, it presents history teachers speeches, specifically relating their training to their understanding of curriculum processes, their reading of the official curriculum, the criticism that manifest, the experiences built daily to deal with the curriculum. In the face of the findings in this research, it is clear that there is little understanding of the curricular debate among teachers and that resistance or acceptance they manifest in relation to the official curriculum is guided by a conception of education that they understand to be critical and disruptive of the official discourse. The practices that they report show critics to the curriculum objectives, specifically to its imposition and linking with the pedagogy of competencies. Teachers defend the need for the curriculum to be standardized across the school network. They incorporate the proposed content, although making remarks to the form of distribution and organization.